Implementing Load-Side Operating Energy Reserves to Improve System Frequency Control Amid the Expansion of Distributed Generation - Mtolo, Dumisani; Sarma, Rudiren; Dorrell, David G. (John Wiley & Sons, 2025)
Eskom, South Africa's national power utility, is transitioning from centralised, large-scale electricity coal generation to a more distributed, small-scale inverter-based renewable generation to reduce greenhouse gas emissions. This shift poses operational challenges, particularly in maintaining power system frequency stability, which relies on real-time balancing of supply and demand. Traditionally, frequency stability has depended on accurate load forecasts, sufficient generation capacity, and energy reserves from large generators to handle disturbances. However, as the number of large generators decreases, energy reserves will also reduce, potentially compromising frequency stability. This paper introduces the concept of integrating small-scale distributed generators to enhance both primary and secondary frequency control. By actively monitoring and managing these inverter-based generators, while accounting for phase balancing and network congestion, the proposed system seeks to improve grid stability, minimise reliance on large generators, and mitigate the risk of secondary frequency drops within an unmanaged inverter-based network (i.e. the high rate of change of frequency (RoCoF) may lead to inverter trips).